Identification of sports injuries in semarang city communities based on gender - Muhammad Muhibbi; Didi Yudha Pranata; Ahmad Teguh Ramadhan; Fekie Adila (Universitas Riau, 2023)
(English)The study aims to determine the type of injury and location of sports injuries experienced by the people of Semarang City based on gender. The survey method used in this study. The population of this study was the people of Semarang who became patients of Seger Waras Massage Clinic. The samples in this study used total sampling techniques. Collect data using questionnaires. Data analysis using frequency statistics. The results showed that sports injuries that occurred in Semarang city people consisted of 1.12% male and 3.06% female neck injuries, 10.82% male shoulders and 15.31% female, male outer elbows 0.87% and 1.02% female, 0.37% male inner elbows and 0% female, 1.99% male and female wrists 12.24%, 0.25% male and female palms 1.02%, male fingers 0.75% and female 2.04%, Back male 5.72% and female 6.12%, waist male 10.07% and female 19.39%, periformis syndrome male 2.74% and female 2.04%, hamstring male 2.99% and female 3.06%, knee male 41.04% and female 21.43%, calf male 1.12% and female 1.02% and ankle male 20.15% and female 12.24%. In conclusion, sports injuries experienced by the people of Semarang City are 14 types of sports injuries and those often experienced by men and women are knee injuries, 330 men (41.04%) have knee injuries and 21 women have knee injuries (21.43%).(Indonesian)Penelitian bertujuan untuk mengetahui jenis cedera dan lokasi cedera olahraga yang dialami masyarakat Kota Semarang berdasarkan jenis kelamin. Metode survei yang digunakan dalam penelitian ini. Populasi penelitian ini adalah masyarakat kota semarang yang menjadi pasien Klinik Pijat Seger Waras. Sampel dalam penelitian ini menggunakan teknik total sampling. Pengumpulan data menggunakan kuesioner. Analisis data menggunakan statistik frekuensi. Hasil penelitian menunjukkan bahwa cedera olahraga yang terjadi pada masyarakat kota semarang terdiri dari cedera leher 1,12% laki-laki dan 3,06% perempuan, cedera bahu 10,82% laki-laki dan 15,31% perempuan, siku luar laki-laki 0,87% dan 1,02% perempuan, siku dalam laki-laki 0,37% dan 0.02% perempuan. % perempuan, pergelangan tangan laki-laki 1,99% dan perempuan 12,24%, telapak tangan laki-laki 0,25% dan telapak tangan perempuan 1,02%, jari tangan laki-laki 0,75% dan perempuan 2,04%, Punggung laki-laki 5,72% dan perempuan 6,12%, pinggang laki-laki 10,07% dan perempuan 19,39%, sindrom periformis laki-laki 2,74% dan perempuan 2,04%, otot paha belakang laki-laki 2,99% dan perempuan 3,06%, lutut laki-laki 41,04% dan perempuan 21,43%, betis laki-laki 1,12% dan perempuan 1,02% dan pergelangan kaki laki-laki 20,15% dan perempuan 12,24%. Kesimpulannya, cedera olahraga yang dialami masyarakat Kota Semarang ada 14 jenis cedera olahraga dan yang paling sering dialami oleh laki-laki dan perempuan adalah cedera lutut, 330 laki-laki (41,04%) mengalami cedera lutut dan 21 perempuan mengalami cedera lutut (21,43%) Copyright © The Author (s) 2023Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.